A comparison between the preferences for oral corrective feedback of teachers and students of Chinese as a second language - Bao, Rui; Wang, Hui (Frontiers in Psychology, 2023)
This study reports on the preferences of teachers and students of Chinese as a second language (CSL) for corrective feedback (CF) and the reasons underlying their preferences. Data was collected from 328 students and 46 teachers through a questionnaire and interviews, and the results showed that CSL students had a strong overall preference for explicit correction and metalinguistic clues, while teachers favored recasts. Moreover, students and teachers significantly varied in their preferences for metalinguistic clues, explicit correction, and clarification requests across error types. A difference was also identified in recasts regarding phonological and lexical errors. Explanations for these variations are attributed to the characteristics of the Chinese language, learner proficiency, teachers’ entrenched beliefs in teaching, and the features of some given CF types. Additionally, the interview data also revealed the different reasons that teachers and students consider when it comes to CF provision. Finally, pedagogical implications for language teachers are discussed.